Adoption of e-assessment technologies to enhance the happiness of academics. Insights from higher learning institutions in Tanzania - Namabira, Judith; Kamanzi, Adalbertus; Chawene, Agnes (African Journal of Education and Practice, 2022)
In an anecdote, a university professor, who has done research on happiness for the rest of her life, invited students to talk about happiness. She gave each one a balloon, asked them to fill them with air, write their names on them, and release them in the air. In a short moment, the whole hall was full of balloons. She then asked each one to get their balloon with their name on. After a struggle of a couple of hours, none got their balloon back. And then she asked them to get each one any balloon, read the name on it, and search for the owner, and give the balloon back to the owner. In less than five minutes, each one had got their balloon. After the exercise the professor concluded: "These balloons are like happiness. We will never find it if everyone is looking for their own. But if we care about The study aims at assessing the happiness of the academics in the higher learning institutions of Tanzania during these times of massification. Data from a total number of 116 academic Whatsapp group members in Tanzania was collected through Google Forms. With the use of the "anchoring vignette" in order to understand the major functions of the academics, the respondents assessed their levels of happiness on a five-ladder Likert scale. The descriptive statistics were used to describe the degree of happiness and the Independent Samples T-Test and the Kruskal-Wallis H Test to test the null hypotheses that gender, positions and working experience of the academics have no influence on the happiness of academics in their functions. The study reveals that the academics are generally happy, but less happy in the activities of marking assessments and exams. The study also revealed that neither gender nor academic positions and working experience significantly impacted on the academics' unhappiness. The universities are urged to do more research on the suitable e-assessments for their students and make use of the available e-assessments technologies in order to reduce the marking pressure for the academics. The higher learning institutions are recommended to institutionalize annual happiness indices and annual education e-technologies' use indices in order to regularly monitor happiness and education e-technologies' use, respectively. The government of Tanzania, through the Ministry in charge of higher education and other educational stakeholders need to promote mechanisms and frameworks to promote research and the use of e-assessments. The paper contributes more knowledge about the reasons to adopt e-technologies in education, on the one hand, and it also enhances knowledge on the e-methods in data collection, on the other hand.